Erotic triangles : Sundanese dance and masculinity in West Java - Spiller, Henry (Chicago : University of Chicago Press, 2010)
In West Java, Indonesia, all it takes is a woman's voice and a drum beat to make a man get up and dance. Every day, men there, be they students, pedicab drivers, civil servants, or businessmen breach ordinary standards of decorum and succumb to the rhythm at village ceremonies, weddings, political rallies, and nightclubs. The music the men dance to varies from traditional gong ensembles to the contemporary pop known as dangdut, but they consistently dance with great enthusiasm. In Erotic Triangles, Henry Spiller draws on decades of ethnographic research to explore the reasons behind this phenomenon.
Discourses of Sundanese dance -- Drumming and power -- Ronggeng and desire -- Dance events and freedom -- The erotic triangle of Sundanese dance -- Triangulating Sundanese dance.
Includes bibliographical references (page 223-238) and index.
Keywords: Dance -- Indonesia -- Jawa Barat; Sundanese (Indonesian people) -- Music; Masculinity in music